Know Your Place, Know Your Calling: Geography, Race, and Kant’s “World-Citizen” - Lu-Adler, Huaping (Studia Kantiana, 2023)
Anthropology and physical geography were among Kant’s most popular and longest running courses. He intended them to give his students the world-knowledge (Weltkenntniß) that they needed in order to be effective world-citizens (Weltbürgern). Much of this indoctrination amounted to teaching Occidental white men, Kant’s default audience, to perceive themselves as uniquely entitled and obliged to work as agents of human progress on the assumption that they, thanks to their geographic location on Earth, were naturally formed as an exceptional race. I trace this perception to a combination of Kant’s lectures and publications. He already indicated it in some of his works from the 1750s and 1760s. He subsequently fleshed it out through a theory of race based on his geography course in conjunction with a pure moral theory, a pragmatic anthropology that complements the moral theory, and a theory of education that builds on those three.